ANALISIS KEBIJAKAN PEMBERDAYAAN MASYARAKAT DALAM PENANGGULANAN KEMISKINAN MELALUI PENGOLAHAN HASIL PERIKANAN DI KABUPATEN TEGAL - Lilik Sulistyowati; Nurhasanah Nurhasanah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The objectives this research were 1) to assess the implication community empowerment program on the performance of technology, social, economic and institutional development of coastal communities, 2) to determine the improvement strategy of empowerment of coastal communities, 3) to provide improvement strategy for coastal communities in Tegal, Central java. Research is using descriptive qualitative method, with research subjects are 150 samples of fisherman in Tegal, central java, Result of this research show, the implementation community empowerment program has triggered changes in social-cultural, technological, economic and institutional development of coastal communities in Tegal. Results of internal and external evaluation showed that 1) their strengths are: potencial age, adecuate level of education dan KUB; 2) their opportunities were: potential of fish resources, communities institutional development, support from govermen instructor and transfer of technologies; 3) their weakness are: lack of technological, lack of capita ,and (4) their theats are: high oprational prices, and labor diversivication. Priority alternative model empowerment for coastal community in Tegal,Central java are 1) development of capital access; 2) development of technology and scale fisheries; 3) capacity development of coastal community institutional; 4) development of fishes processing diversification and 5) community base management of fisheries